Efficacy of ixazomib, lenalidomide, dexamethasone regimen in daratumumab-exposed relapsed/refractory multiple myeloma patients: A retrospective analysis - Fric, Dominik; Stork, Martin; Boichuk, Ivanna; Sandecka, Viera; Adam, Zdenek; Krejci, Marta; Ondrouskova, Eva; Fidrichova, Anna; Radova, Lenka; Knechtova, Zdenka; Jarosova, Marie; Pour, Ludek (European journal of haematology, 2024)
We performed retrospective analysis of relapsed/refractory multiple myeloma (RRMM) patients previously exposed to daratumumab treated with ixazomib, lenalidomide, dexamethasone (IRd) regimen in real clinical practice. Our aim was to evaluate efficacy of IRd in these patients and select a subset of patients that would benefit from this treatment the most. In total, we analyzed 43 daratumumab-exposed RRMM patients treated in our center. Minimal response or better was achieved by 53.5% of patients from the cohort. Median progression free survival (PFS) was 4.56 months (95% CI: 2.56, 8.03) and median overall survival (OS) was 28.92 months (95% CI: 5.4, NR). Duration of response (DOR) was evaluable in 28 patients and reached a median of 21.3 months (95% CI: 6.85, NR). Next, we evaluated hazard ratios (HR) for OS and PFS. There was improved OS in patients that were not-triple refractory or worse (HR = 0.39, 95%Cl (0.14; 1.10), p = .07) and in patients, that had less than three previous lines of treatment (LOT) (HR = 0.13, 95%Cl (0.03; 0.6) p = .003). Similar to OS, there was improved PFS in patients, that were not triple-refractory or worse (HR = 0.52, 95%Cl (0.25; 1.10), p = .08). We concluded, that the best survival benefit for RRMM patients pretreated with daratumumab to IRd regimen was observed in patients that were not triple-refractory and had less than three previous lines of treatment (LOT). The DOR in these patients was 21.3 months (95% CI: 6.85, NR).
Keywords: dexamethason; glycin; lidé; Middle Aged; výsledek terapie; Adult; Recurrence; chemorezistence; Drug Resistance, Neoplasm; Female; Multiple Myeloma; Retreatment; Dexamethasone; retrospektivní studie; lenalidomid; Humans; Antibodies, Monoclonal; protokoly protinádorové kombinované chemoterapie; recidiva; monoklonální protilátky; opakovaná terapie; lidé středního věku; Glycine; mužské pohlaví; sloučeniny boru; mnohočetný myelom; daratumumab; Lenalidomide; ženské pohlaví; Aged, 80 and over; Treatment Outcome; senioři nad 80 let; Male; Aged; Retrospective Studies; dospělí; Antineoplastic Combined Chemotherapy Protocols; ixazomib; relapsed/refractory multiple myeloma; Boron Compounds; senioři